Relevansi Parliamentary Threshold terhadap Pelaksanaan Pemilu yang Demokratis - Sunny Ummul Firdaus (Jurnal Konstitusi, 2016)
General Election as a means to realize the ideal of democracy does    not merely aim to determine who will get the position in the parliament but it also should represent the sovereignty of the people. In the 2009 General Election, however, parliamentary threshold was prevailed and implemented. This regulation is included on Article 202 The General Election Act number 10/2008 which stated that political party of General Election participant must fulfil at least an amount of 2.5% of total valid national vote to be included in the representation determination of the House of Representative.A number of Indonesian peoples objected the rule. This is because parliamentary threshold deemed to be potentially demolished the political right of the people. Besides, the implementation of parliamentary threshold in bottom level considered to have some potential horizontal conflict because, for example, if someone voted as a selected candidate but they do not fulfil the parliamentary threshold, this particular candidate cannot obtain a seat in the parliament. This can be seen in the petition of judicial review to the Constitution Court regarding this parliamentary threshold regulation.It can be concluded  that  the  relevance  of  parliamentary  threshold to democratic General Election execution can not be separated from the mechanism and reasons in determining the the amount of threshold numbers in said rule. Requirement for determining the threshold is not merely based on a reason to strengthen presidential system chosen by the Indonesian people. In this case, the people’s voice should not be represented merely by the parliamentary number having position in the House of Representative. If this happens, then there will be some concerns of the emergence of political interest to strengthen the position of a particular political party in the  parliament.